Analisis kebutuhan SI dengan pendekatan value chain: indonesia - Pratama, Yusuf Hendra (STMIK Palangkaraya, 2020)
SMK (Vocational High School) Negeri 5 Mataram is a school based on arts and culture. This school has some Information System (IS) that applied to the educational system, e.g, electronic report features of learning result (E-Rapor) and website. In its implementation, the IS was unable to support schools to provide the newest information due to the large amounts of data management, the data waos changed routinely and repetitive, it often created difficulties to provide information, especially because of the academic data activity is still using a manual processing system. Based on those problems above, the needs analysis of IS was conducted using value chain method. This method used to construct and formulates some strategies that possible to apply. The result, there were seven new application portfolios, i.e PSB Online, Financial Apps, Inventory Apps, E-Locker, E-Library, E-Learning, and Academic Information System. And two applications had improved, School Website and E-Report.